Effect of Oxalic Acid, Na+, NH4+, and Fe3+ on Release of Fixed Potassium and Basal Distance of Smectite in Smectitic Soils - Dedi Nursyamsi (JOURNAL OF TROPICAL SOILS, 2009)
Laboratory experiment aimed to study effect of oxalic acid, Na+, NH4+, and Fe3+ on the release of fixed potassium and basal distance of smectite in smectitic soils was conducted in Laboratory of Soil Sciences, Graduate School of Agriculture, Kyoto University, Japan. The experiment used four of topsoil samples of Typic Hapludalfs (B1),  Chromic Endoaquerts (B2), Typic Endoaquerts (B3), and Typic Haplustalfs (B4) taken from Jonggol (Bogor), Sidareja (Cilacap), Padas (Ngawi), and Todanan (Blora) respectively. This experiment also used randomized completely block design, six treatments, i.e.: control (water), 1 N of oxalic acid, (oxalic acid+NaOH) pH=7, Na+, NH4+, and Fe3+ respectively and they were replicated three times. After extracting the samples, potassium concentration in supernatant was measured by Atomic Absorption Spectrophotometer (AAS) method and basal distance of smectite in clay paste was measured by X-Ray Diffraction (XRD) method. The result showed that oxalic acid, (oxalic acid+NaOH) pH=7, Na+, NH4+, and Fe3+ increased the release of fixed potassium by clay in all tested soils about 24.63-3744%, 31.88-45.38%, 25.37-48.35%, 27.48-42.32%, and 28.17-35.49%, respectively. Among the treatments, (oxalic acid+NaOH) pH=7 was the most effective in releasing fixed K at Alfisols, while Na+ at Vertisols.  Oxalic acid+NaOH pH=7, Na+, and Fe3+ increased the basal distance of smectite in the soils about 10.41%, 11.48%, and 15.30%, respectively. Among the treatments, Fe3+ was the highest in increasing the basal distance of smectite in the soils.